Keynes, Kalecki and Minsky - Post Keynesian champions in comparison or: Joining forces, horses for courses or the necessity of discrimination? - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2024)
The push to pluralise the economic discipline involves making informed decisions about which paradigm to adopt, requiring a deep understanding of each paradigm's characteristics and affiliations. Once paradigmatic choices are made, different theories can either collaborate effectively or require clear discrimination if they belong to distinct paradigms. Therefore, economic theories and models need to be compared with respect to their paradigmatic localisation. Based on a hermeneutic comparison, the common assessment that the champions of Post Keynesian economics - John Maynard Keynes, Michal Kalecki and Hyman P. Minsky's share a unified Post Keynesian paradigm must be questioned. Kalecki's economics, with its closed system perspective, differs fundamentally from Keynes's open system approach. This distinction suggests that Kalecki's work is not merely a variant of Keynes's monetary production paradigm but could align more closely with new-Keynesian imperfect competition models based on the traditional real-exchange paradigm. Minsky's dynamic approach, however, shares Keynes's open system ontology, making them compatible. This analysis suggests that the term 'Post Keynesianism' might inaccurately imply a coherence that does not exist.
Keywords: B40; B59; E12; P59; 330; Keynes's economics; Kalecki's economics; Minsky's economics; paradigms; comparison